Application of molecular interaction volume model on removing impurity aluminum from metallurgical grade silicon by vacuum volatilization. (April 2015) - Liu, Kai; Wu, Jijun; Wei, Kuixian; Ma, Wenhui; Xie, Keqiang; Li, Shaoyuan; Yang, Bin; Dai, Yongnian
Abstract: The vacuum volatilization of aluminum from silicon melt is studied by the molecular interaction volume model (MIVM) in this paper. The activities and activity coefficients of components in the Si–Al binary melt were investigated based on the MIVM and the results show that the predicted values of activities are in good agreement with the experimental data. The infinite dilution activity coefficients of Al in the Si–Al binary melt at 1673–2273 K is expressed as log γ Al ( 1 ) ∞ in Si  = 7.66983 × 10 −5 T -0.43563. The separation coefficient β Al, the volatilization rate V Si and the removal efficiency η Al are calculated using the activity coefficients γ Si, γ Al and the vapor–liquid equilibrium diagram of Si–Al binary melt. In order to decrease the loss of silicon volatilization and enhance the separation of Al from Si–Al binary melt, the optimal temperature and time conditions for Al volatilization are 1773–1973 K and 3–5 ks, respectively. The experimental results show that the removal efficiency of Al is 99.67% by vacuum directional solidification under the optimal condition of vaporization temperature 1873 K, chamber pressure 10 −3  Pa, holding time 3.6 ks and solidification rate 10 μm/s. Highlights: MIVM is reliable for predicting the activities for the Si–Al binary melt. The calculated activities of Al and Si are in agreement with the experimental. The optimal process conditions for Al volatilization were obtained. The removal efficiency of Al reaches 99.67% from silicon melt.